Expanding Peace Journalism Comparative and Critical Approaches - Shaw, Ibrahim Seaga; Lynch, Jake; Hackett, Robert A. (Sydney University Press, 2011)
Expanding Peace Journalism: Comparative and Critical Approaches draws together cutting-edge contributions from 17 international writers to this rapidly emerging field of research. Media coverage of conflicts is propagandistic and commonly portrays two elite actors contesting a single goal of 'victory'. This major new text explores and interrogates peace journalism as a significant challenge to this hegemonic discourse, which has been advocated and elaborated over the recent years in journalism, media development and academic spheres. Expanding Peace Journalism traces boundaries and links with the adjacent fields including alternative media, social movement activism and media democratisation. It includes case studies - from the media of countries including Australia, Canada, Guatemala, India, Nigeria, Norway, Sweden and the US - and explores connections with human rights, as well as Indigenous and women's rights activism.